2020
DOI: 10.1073/pnas.1900015117
|View full text |Cite
|
Sign up to set email alerts
|

Superrepellency of underwater hierarchical structures on Salvinia leaf

Abstract: Biomimetic superhydrophobic surfaces display many excellent underwater functionalities, which attribute to the slippery air mattress trapped in the structures on the surface. However, the air mattress is easy to collapse due to various disturbances, leading to the fully wetted Wenzel state, while the water filling the microstructures is difficult to be repelled to completely recover the air mattress even on superhydrophobic surfaces like lotus leaves. Beyond superhydrophobicity, here we find that the floating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 28 publications
0
89
0
Order By: Relevance
“…71,90 As this plant lives on the surface of the water, its air-retention ability becomes important when accidentally immersed in water to maintain its respiration and photosynthesis processes. 76 This has been attributed to the external layer of densely packed hairlike features on the leaf surface (Fig. 6h).…”
Section: The Salvinia Effectmentioning
confidence: 91%
See 1 more Smart Citation
“…71,90 As this plant lives on the surface of the water, its air-retention ability becomes important when accidentally immersed in water to maintain its respiration and photosynthesis processes. 76 This has been attributed to the external layer of densely packed hairlike features on the leaf surface (Fig. 6h).…”
Section: The Salvinia Effectmentioning
confidence: 91%
“…self-cleaning of Lotus leaves), as well as the ability to maintain an air layer while underwater for different periods, depending on their needs. 71,[74][75][76][77][78] As many insects have life cycles connected to water, their bodies have evolved accordingly to repel water, which is necessary for their breathing and additional functionality. 77 A thorough examination of surfaces found in nature reveals key design features required for airlayer stability underwater.…”
Section: Underwater Stable Systems From Naturementioning
confidence: 99%
“…Likewise, another study reported the ability of sixteen reproduced plant surfaces to affect the spatial distribution of Pseudomonas aeruginosa attachment [ 63 ]. Superhydrophobic characteristics of plants are also exploited for self-cleaning and drag-reducing effects [ 81 , 82 ]. For example, Xiang et al [ 81 ] fabricated a biomimetic Salvinia molesta surface using a 3D printing approach, which imitates the floating fern’s superrepelent capability.…”
Section: Natural Surfacesmentioning
confidence: 99%
“…Superhydrophobic characteristics of plants are also exploited for self-cleaning and drag-reducing effects [ 81 , 82 ]. For example, Xiang et al [ 81 ] fabricated a biomimetic Salvinia molesta surface using a 3D printing approach, which imitates the floating fern’s superrepelent capability. Similarly, the rice leaf anisotropic structure has been implemented for such properties [ 82 ].…”
Section: Natural Surfacesmentioning
confidence: 99%
“…Therefore, the surface of Salvinia leaves is considered as a biological model for technological air-retaining surfaces. [5,[40][41][42][43][44][45][46][47][48][49] In order to have an effective air retention, the upper side of the leaves is covered with elastic, superhydrophobic, eggbeater-shaped trichomes (later called "hairs") (see Figure 1a,b). The backside of the leaf is hydrophilic, and therefore staying in permanent direct contact with water.…”
Section: Introductionmentioning
confidence: 99%